Blue [compact disc, unabridged] : a novel - Steel, Danielle (Brilliance Audio, 2016)
Ginny Carter was once a rising star in TV news, married to a top anchorman, with a three-year-old son and a full and happy life in Beverly Hills. Then her whole world is dissolved in a single instant on the freeway two days before Christmas. In the aftermath, she pieces her life back together and tries to find meaning in her existence as a human rights worker in the worst areas around the globe. Then, on the anniversary of the fateful accident, and wrestling with the lure of death herself, she meets a boy who will cause her life to change forever yet again.